Siculobata (Paraleius) leontonycha - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Siculobata (Paraleius) leontonycha (Berlese, 1910) * Material – New record for Turkey. Four specimens in Karadedeoğlu Village, Tekkeyaylası Forest Area, Taşköprü-Kastamonu, N 41° 22′ 23.26′′, E 34° 24′ 22.11′′, alt. = 1187 m, 23 August 2018; two specimens in Alasökü Village Forests, Taşköprü-Kastamonu N 41° 20′ 09.64′′, E 34° 25′ 58.98′′, alt. = 1327 m, 10 June 2018, tree bark and debris of P. nigra and P. sylvestris. Global distribution – Holarctic. Ecology – Bark debris around the trunks, in pathways of woodborer beetles. Remarks – Measurements: Weigmann (2006) reports size of S. leontonycha as 435–500 µm. Travé (1960), Wunderle et al. (1990) and Perez-Iňigo (1993) also indicate larger individuals (440–500 µm, 435–480 µm and 440–500 µm respectively), while Ghilarov and Krivolutsky (1975) and Mahunka (1996) do not indicate body size at all. All Turkish individuals are smaller (360–365 × 215–220 µm) than reported. The rest of the characters match with provided descriptions. The species is known to be arboricolar (Weigmann 2006). Turkish records prove this habitat preference by finding all individuals on bark of pine tree species. Checklist of oribatid mites of Georgia (Murvanidze and Mumladze 2016) report presence of this species in soils of alpine meadow after the catalogue of Caucasian oribatids of Shtanchaeva and Subias (2010), however, this report is a mistake, because the catalogue does not list S. leontonycha at all and Georgian record can be discarded.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 266, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Siculobata leontonycha; Arthropoda; Arachnida; Animalia; Hemileiidae; Biodiversity; Sarcoptiformes; Taxonomy; Siculobata; 15. Life on land